Bearing the wrong identity: A case study of an Indo-Pacific common shallow water sponge of the genus Neopetrosia (Haplosclerida; Petrosiidae) - Setiawan, Edwin; Erpenbeck, Dirk; Wörheide, Gert; de Voogd, Nicole J. (Zootaxa, 2018)
Sponges of the order Haplosclerida are often abundant and characteristic components of Indo-Pacific reefs, but are often misidentified, because of the lack of clear distinctive morphological characters. Neopetrosia exigua is an example of a haplosclerid sponge that is very common in Indonesian shallow coral reef environments but bears several different names. In the present study we investigated type material of several Indo-Pacific Neopetrosia species with a similar morphology and examined freshly collected specimen materials including specimens that are deposited at several institutions. In addition, we used molecular phylogenetic methods for assisting the morphological examinations. We conclude that the true identity of Neopetrosia exigua should be Neopetrosia chaliniformis. Likewise, N. exigua and N. pacifica should be considered as junior synonyms of N. chaliniformis. In conclusion, we advocate that molecular barcoding could significantly aid on sponge species’ delimitation that possess limited morphological characters.